Perilaku Memilih Pemilih Pemula Dalam Pemilihan Kepala Daerah Dan Wakil Kepala Daerah Di Kota Semarang Tahun 2020 - Fazalani, Lalu Agsal; Prihatmoko, Joko J (JURNAL LANSKAP POLITIK, 2022)
This study aims to explain the extent to which novice voters in the city of Semarang are actively involved in the implementation of the 2020 Pilkada, as well as to find out what factors can influence the behavior of novice voters in making choices. This research uses descriptive qualitative method. Researchers use this method in order to more deeply analyze the voting behavior of novice voters. Data collection techniques were taken through in-depth interviews with related sources, literature studies, and field observations. This is intended so that the data obtained can be more comprehensive and make it easier to map the area of election factor analysis for novice voters. The results showed that in general, novice voters in the city of Semarang were classified as rational voters, these novice voters chose regional head candidates based on considerations of past performance or the vision-mission carried by the candidate.